Mechanical, thermal and ultrasonic properties of AgRE intermetallics at different temperatures. (1st February 2022) - Khan, Mohd Aftab; Kumar, Mahendra; Yadav, Chandreshvar Prasad; Pandey, Dharmendra Kumar
ABSTRACT : The present study incorporates computation of elastic, ultrasonic and thermal properties of B2 structured AgRE (RE = Sm, Tb, Ho, Tm) intermetallics in the temperature range 300–1100 K. Initially, elastic constants were determined using the potential model approach. Later on, ultrasonic velocities were obtained in the same temperature range for wave propagation along <100> and <111> crystallographic directions. Along with it, Debye temperature, specific heat at constant volume, thermal energy density, thermal conductivity, thermal expansion coefficient and melting temperature were also calculated for selected intermetallics. The obtained results were compared and analyzed for the justification and application of materials.